دور الاٍتصال التسويقي في السلوك الشرائي للمستهلك دراسة ميدانية على عينة من طلبة جامعة المسيلة - محمد بوصبع (جامعة محمد بوضياف المسيلة, 2025)
تهدف هذه الدراسة إلى تحليل دور الاتصال التسويقي في ترقية السلوك الاستهلاكي لدى طلبة قسم الإعلام بجامعة المسيلة، باعتبارهم فئة شبابية تتعرض بشكل مكثف للرسائل التسويقية عبر مختلف الوسائط، خاصة الرقمية منها. اعتمدت الدراسة على المنهج الوصفي التحليلي، حيث تم توزيع استبيان على عينة من طلبة الإعلام لقياس مدى تأثر سلوكهم الاستهلاكي بمضامين الاتصال التسويقي، من حيث أساليب الشراء، تفضيل العلامات التجارية، وتحديد الحاجات والرغبات. أظهرت النتائج أن الاتصال التسويقي يلعب دورًا ملحوظًا في تشكيل قرارات الطلبة الشرائية، خاصة عبر وسائل التواصل الاجتماعي، التي تمثل القناة الأكثر تأثيرًا. كما تبين وجود وعي متفاوت بين الطلبة بخصوص طبيعة التأثيرات التسويقية، إلا أن الكثير منهم يتأثرون بالعروض، التصاميم، والرموز الإقناعية المستخدمة في الحملات الترويجية This study aims to analyze the role of marketing communication in promoting consumer behavior among students of the Media Department at the University of M’sila, considering them a youth segment heavily exposed to marketing messages through various media channels, especially digital ones. The study adopted a descriptive-analytical approach, utilizing a questionnaire distributed to a sample of media students to assess the extent to which their consumer behavior is influenced by marketing communication content, particularly in terms of purchasing habits, brand preferences, and the identification of needs and desires. The findings revealed that marketing communication plays a significant role in shaping students’ purchasing decisions, especially through social media, which emerged as the most influential channel. The results also showed varying levels of awareness among students regarding the nature of marketing influences; however, many are still affected by promotional offers, visual designs, and persuasive symbols used in marketing campaigns.